200 Years To Political Economy in Vilnius University - Laumenskaitė, Egidija (Ekonomika, 2004)
This paper gives a concise overview of the development of the economic thought in Lithuania mentioning the very special event in the history of the economic science - the establishment of the Department of Political Economy in Vilnius University in 1803 as the first Department of Political Economy in the world.